2012
DOI: 10.1007/s11136-012-0234-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-severe nocturnal hypoglycemic events: experience and impacts on patient functioning and well-being

Abstract: PurposeNon-severe nocturnal hypoglycemic events (NSNHEs) are hypoglycemic events that occur during sleep but do not require medical assistance from another individual. This study was conducted to better understand the NSNHEs as patients actually experience them in their daily life, and how they impacted functioning and well-being.MethodsNine focus groups were held in four countries with diabetics (Type 1 and Type 2) who had experienced an NSNHE within the previous month: France (2 groups); Germany (2 groups); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 12 publications
2
55
1
Order By: Relevance
“…21,22 Non-severe hypoglycaemia is also associated with a significant reduction in quality of life and accounts for a substantial reduction in work productivity. [23][24][25] The current pooled, post hoc analysis of patient-level data from n=906 and n=1,297; Fonseca study 31 n=792 and n=1,084, respectively). In addition, the previous study only reported symptomatic hypoglycaemia (including confirmed symptomatic and severe symptomatic), 31 whereas the current analysis provides additional information regarding rates of overall, daytime, nocturnal and severe hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Non-severe hypoglycaemia is also associated with a significant reduction in quality of life and accounts for a substantial reduction in work productivity. [23][24][25] The current pooled, post hoc analysis of patient-level data from n=906 and n=1,297; Fonseca study 31 n=792 and n=1,084, respectively). In addition, the previous study only reported symptomatic hypoglycaemia (including confirmed symptomatic and severe symptomatic), 31 whereas the current analysis provides additional information regarding rates of overall, daytime, nocturnal and severe hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the impact of NSHE, a survey was developed based on the literature, expert input and interviews with 78 persons with either type 1 diabetes or type 2 diabetes who had recently experienced an NSHE, in nine focus groups across four countries (USA, UK, Germany and France)10. Survey items were developed based on a qualitative analysis of the expert input and the persons’ with diabetes interviews, and cognitively debriefed and pilot tested in English in nine persons who met the same eligibility criteria as the focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28] Affected individuals felt tired, slow, depressed and restless on the day after nocturnal hypoglycaemia. [29][30][31] Negative effects have been reported on work attendance, performance and productivity.…”
Section: How Have the Eu Driving Regulations Changed In The Uk From Jmentioning
confidence: 99%
“…[29][30][31] Negative effects have been reported on work attendance, performance and productivity. [28][29][30][31] There is evidence that hypoglycaemia during sleep is relevant to a person's ability to function normally after awakening, whether this is in the morning after nocturnal hypoglycaemia or at some other time of day. Following an episode of severe nocturnal hypoglycaemia, drivers should be advised to avoid driving the following day, at least in the hours after awakening.…”
Section: How Have the Eu Driving Regulations Changed In The Uk From Jmentioning
confidence: 99%